Variants of Concern Are Overrepresented Among Postvaccination Breakthrough Infections of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in Washington State. (24th June 2021) - McEwen, Abbye E; Cohen, Seth; Bryson-Cahn, Chloe; Liu, Catherine; Pergam, Steven A; Lynch, John; Schippers, Adrienne; Strand, Kathy; Whimbey, Estella; Mani, Nandita S; Zelikoff, Allison J; Makarewicz, Vanessa A; et al.
Abstract: Across 20 vaccine breakthrough cases detected at our institution, all 20 (100%) infections were due to variants of concern (VOCs) and had a median Ct of 20.2 (IQR, 17.1–23.3). When compared with 5174 contemporaneous samples sequenced in our laboratory, VOCs were significantly enriched among breakthrough infections ( P < .05).